Summaries of central bank policy deliberations: A Canadian context - Monica Jain; Walter Muiruri; Jonathan Witmer; Sharon Kozicki; Jeremy Harrison (Bank of Canada, 2023)
This paper provides the context, rationale and key considerations that informed the Bank of Canada's decision to publish a summary of monetary policy deliberations. It includes an analysis of how other central banks disclose minutes and summaries of their monetary policy deliberations. Publishing a summary of deliberations could enhance transparency, accountability and credibility and also reinforce the Bank's independence. However, these benefits must be balanced against the potential for constraints on internal debate or the sending of mixed messages about the Bank's outlook and decisions. The Bank of Canada Act empowers the Governor to make decisions, but in practice, decisions are made by consensus among members of the Bank's Governing Council. This decision-making by consensus could have implications for what could or should be included in a summary. In the Canadian context, assuming the Bank will provide additional information, we also discuss some advantages and disadvantages of providing a summary of deliberations as a separate communication product or as an enhancement to current communications products.
Keywords: D83; E58; 330; Monetary policy communications